Investigation of organic contaminants in field-cultivated vegetables receiving recycled water and biosolids applications - Nicole M. Dennis; Audrey J. Braun; Zahra Mafishiraz; Jay Gan (Environment International)
Tertiary treated wastewater (e.g., recycled water) and treated sewage sludge (e.g., biosolids) are increasingly recognized as valuable yet underutilized resources in agriculture. While recycled water and Class A biosolids provide agronomic benefits, they also contain numerous unregulated organic chemicals (UOCs) at trace levels. Field-derived data on UOC fate and uptake into food crops remains scarce. This large-scale field study investigated the accumulation of 44 priority UOCs, including pharmaceuticals, personal care products, plasticizers, flame retardants, and illicit drugs, in radish, broccoli, and spinach grown with recycled water and Class A biosolids at 0, 0.430, 1.08, and 2.15 metric tons/ha. Using validated UPLC-ESI-MS2 methods, 15 UOCs were detected in edible tissues at concentrations ranging from 2.10 to 994 ng/g dry weight. Cannabinoids, methamphetamine, phthalates, and fragrances were most frequently detected. Three PFAS compounds were present in the inputs but not detected in vegetable samples. Estimated adult dietary intake of UOCs totaled 277 µg/yr, or 0.011 µg/kg bw/d for a 70 kg person, based on U.S. EPA standardized consumption data. Although most UOCs lack chronic toxicity thresholds, available therapeutic and acute effects levels suggest the estimated exposure is several orders of magnitude lower. These values were presented for context only and do not imply safety or replace formal risk assessment. Crop responses varied by species, with radish biomass increasing at lower biosolids rates and spinach decreasing at higher rates. These results provide field-based insights into UOC accumulation in food production systems to support safe, sustainable use of recycled resources in a circular economy, while emphasizing the need for formal risk assessment.